Automatic Evaluation of Spatial Disorientation (Advances in Military Technology, 2018)
The paper discusses the automated detection of spatial disorientation from recorded flight data. The first part of the paper briefly introduces middle ear function and its influence on spatial disorientation. The specially developed simulator and aerodrome manoeuvre flown by the pilot during the experiment is also mentioned. The second part of the paper analyses the recorded data from experimental flights and proposes an algorithm for the automatic evaluation of spatial disorientation. An example graphical interpretation of the recorded data is provided with a clear explanation of the important parameters. At the end of the paper, the most important conclusions of the work are presented.
Keywords: flight illusion; detection; simulator; spatial disorientation